Educating nursing students for cultural competence in emergencies: a randomized controlled trial - Yosef Kula; Odeya Cohen; Neta Clempert; Orli Grinstein-Cohen; Ortal Slobodin (BMC, 2021)
Abstract Background Racial and ethnic minorities suffer significantly more than others in the wake of disasters. Despite the growing recognition of the importance of culturally competent health services, systematic cultural competence training in the medical education system is still scarce, especially in the field of emergency. The current study aimed to examine the effectiveness of an online culturally informed intervention for increasing cultural competence in emergencies among nursing students. Methods A randomized controlled trial was used to test the intervention effectiveness in increasing nursing students' cultural competence in four domains: attitudes, knowledge, skills, and encounters. The study included 72 undergraduate nursing students recruited from two academic institutes. Participants were randomized (1:1 ratio) to an intervention (n = 34) and control group (n = 38). The study adheres to the Consolidated Standards of Reporting Trials (CONSORT). Data analysis was based on multivariate analysis of variance with repeated measures, followed by post hoc analyses with Bonferroni correction for multiple comparisons. Results Results showed that the intervention was effective in increasing the participants' culturally competent knowledge. The effect of the intervention on the skills domain approached significance. No group differences were identified in the attitudes and the encounters domains. Conclusions An online culturally informed intervention, incorporated in the curriculum, was effective in enhancing the cognitive aspect of cultural competence (especially at the basic knowledge and understanding levels), but not other domains. Our results encourage the development of future intervention programs that are based on a deep understanding of local values, needs, and preferences.